Risk Perception of Skin Cancer at a High-Altitude Hospital - Huanca Huirse, Nuria Leticia (2020)
Objective: To determine the level of risk perception of skin cancer in a population from Cusco. Materials and methods: It is an observational descriptive cross-sectional study and was aplied in a skin cancer screening campaign in Cusco. The applied questionnaire was designed and validated by Morales-Sánchez M and Cols, and it measures the risk perception of skin cancer. The reported Cronbach's alpha value is 0.824. Results: The majority of patients were female (64.7%), average age was 44.9 years (SD: 14.2) and the 51.0% had higher education level. The median hours of sun exposure was 4 (95% CI: 1-6), the most frequent origin was from Cusco (77.6%) and most of the population have normal risk perception of skin cancer (65.8%). Conclusion: The risk perception of skin cancer was normal in the majority of the population. Keywords: Skin Neoplasms, Perception, Health Behavior, Attitude